(3GdLhGeYs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s
(3ChdgG (B:s
(3ZQVg ai gPG GdcJGH GdeJQLe HcJGH GdSeGA hGdYGde GdeJcde ai GdCLSGe GdHSjWI s
(3BNQgG (B:s
(3fLRJ GdebGdI GdQGHYI hJeGegG ef GdcJGH GdeJQLe GdSeGA hGdYGde s
(3eUOQ GbJfGA GdCUd (B:s
(3CSHGfjG (B- (3eOQjO (B(5000) s
Keywords: (3GdadSaI hGdefWbs